Le processus spirituel des femmes qui accouchent : théorisation ancrée sur l’expérience de l’accouchement vaginal au Québec (Canada) - Marie-Noëlle Bélanger-Lévesque (Études Caribéennes)
Like the life-death passage, the passage from the uterine world to the one we know is mysterious and has been throughout history and cultures surrounded by ritual practices and belief systems. Is the place of spirituality still relevant in contemporary delivery room, especially in societies like Quebec, where the last decades have seen profound changes in religious practice and spiritual sentiment? In this article, the doctoral thesis results, based on the constructivist grounded theory approach, illustrate the “spiritual process” of women during vaginal childbirth, in four stages: “facing the unknown”, “diving” (spiritual affirmation), “feeling something greater than me inside me” (spiritual experience) and “giving birth to myself” (spiritual transformation).